Managing future air quality in megacities: Co-benefit assessment for Delhi. (August 2018) - Bhanarkar, Anil D.; Purohit, Pallav; Rafaj, Peter; Amann, Markus; Bertok, Imrich; Cofala, Janusz; Rao, Padma S.; Vardhan, B.Harsha; Kiesewetter, Gregor; Sander, Robert; Schöpp, Wolfgang; Majumdar, Dipanjali; et al.
Abstract: Urbanization, population and economic growth in Indian megacities like Delhi have resulted in an increase in energy and transportation demand leading to severe air pollution and related health impacts, as well as to the rapid growth in the greenhouse gas emissions. In this study, an integrated assessment of air quality and climate policies for Indian cities – with a particular focus on National Capital Territory of Delhi, has been carried out. We have developed emission inventory of air pollutants and greenhouse gases for the base year (2010) and evaluated the impact of current policies on emission projections by 2030 in the business-as-usual scenario. Emissions of coarse and fine particulate matter are projected to be 51% and 15% higher in 2030 as compared to present. As the current legislations do not indicate progress towards the achievement of the Indian National Ambient Air Quality Standards in Delhi, we explored the effectiveness of additional emission control strategies with either advanced end-of-pipe emission controls or low carbon policies. Relative to the baseline scenario, the set of alternative policy strategies would reduce emissions rapidly in 2030. The results revealed that air quality policies under various scenarios could also have co-benefits of reducing carbon emissions. At the same time, the results suggest that low carbon policies would be more efficient to cut emissions as compared to advanced end-of-pipe emission control policies. However, their implementation could be limited by the availability of clean fuels. In the climate policy scenario, carbon emission in 2030 is estimated to decrease by 19% relative to baseline. Additional controls combined with low carbon policies like controlling non-industrial emissions create an opportunity to further enhance the scope for co-benefits and to attain the air quality standards in Delhi. Highlights: Emission inventory of air pollutants and greenhouse gases for Delhi. Emission scenarios for Delhi are analyzed using GAINS-City model. By 2030, without additional measures, PM2.5 emissions will increase by 15%. Low carbon policies combined with advanced end-of-pipe measures are required to improve air quality. Air quality policies result in co-benefits towards reductions of greenhouse gas emissions.